Assessment of molybdenum application on soybean physiological characteristics in maize-soybean intercropping - Jamali, Zameer Hussain; Ali, Shahzaib; Qasim, Muhammad; Song, Chun; Anwar, Muhammad; Du, Junbo; Wang, Yu (Frontiers in Plant Science, 2023)
Soybean is a leguminous crop known for its efficient nitrogen utilization and ease of cultivation. However, its intercropping with maize may lead to severe reduction in its growth and yield due to shading effect of maize. This issue can be resolved by the appropriate application of essential plant nutrient such as molybdenum (Mo). Aim of this study was to assess the effect of Mo application on the morphological and physiological characteristics of soybean intercropped with maize. A two-year field experiment was conducted for this purpose, and Mo was applied in the form of sodium molybdate (Na2MoO4), and four different levels were maintained i.e., 0, 60, 120 and 180 g ha-1. Soybean exhibited varying responses to different levels of molybdenum (Mo) application. Notably, in both sole and intercropped cropping systems, the application of Mo at a rate of 120 g ha-1 demonstrated the highest level of promise compared to other application levels. However, most significant outcomes were pragmatic in soybean-maize intercropping, as application of Mo @ 120 g ha-1 significantly improved soybean growth and yield attributes, including leaf area index (LAI; 434 and 441%), total plant biomass (430 and 461%), transpiration rate (15 and 18%), stomatal conductance (9 and 11%), and yield (15 and 20%) during year 2020 and 2021 respectively, as compared to control treatment. Similarly, Mo @ 120 g ha-1 application resulted in highest total grain yield (626.0 and 725.3 kg ha-1) during 2020 and 2021 respectively, which exceeded the grain yields of other Mo levels under intercropping. Moreover, under Mo application level (120 g ha-1), grain NPK and Mo contents during years 2020 and 2021 were found to be 1.15, 0.22, 0.83 and 68.94 mg kg-1, and 1.27, 0.25, 0.90 and 72.18 mg kg−1 under intercropping system increased the value as compared to control treatment. Findings of current study highlighted the significance of Mo in enhancing soybean growth, yield, and nutrient uptake efficiency in maize-soybean intercropping systems.